2005
DOI: 10.1017/s0265021505000487
|View full text |Cite
|
Sign up to set email alerts
|

Pseudocholinesterase activity increases and heart rate variability decreases with preoperative anxiety

Abstract: Preoperative anxiety increases plasma cholinesterase activity and decreases HR variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Some studies have reported no differences (Dishman et al, 2000;Hughes and Stoney, 2000;Shinba et al, 2008;Tulen et al, 1996). However, the most consistent finding is that anxiety and depressed mood are related to low levels of HF during exposure to stress (Hughes and Stoney, 2000;Ledowski et al, 2005;Light et al, 1998;Shinba et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported no differences (Dishman et al, 2000;Hughes and Stoney, 2000;Shinba et al, 2008;Tulen et al, 1996). However, the most consistent finding is that anxiety and depressed mood are related to low levels of HF during exposure to stress (Hughes and Stoney, 2000;Ledowski et al, 2005;Light et al, 1998;Shinba et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Using a randomization table (a table of random numbers), eligible subjects were randomly assigned into one of two groups: a control group with no music or a treatment group that listened to the music of their choice during surgery. [17][18][19][20] The VAS is a horizontal line with a scale ranging from "no anxiety at all" to "extremely anxious." The STAI has been used extensively in anxiety-related research and clinical practice as a standard measurement tool for assessment of anxiety.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that the one-item question adequately measures current anxiety and significantly correlates with STAI. [17][18][19][20] The VAS is a horizontal line with a scale ranging from "no anxiety at all" to "extremely anxious." The researcher orally instructed the patient in the following manner, "Please mark anywhere along this line to show how anxious you feel right now.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, Fuller (1992) has reported a reduction in heart rate, and an increase in LF and HF powers in low trait anxiety as compared to high trait anxiety participants. Ledowski et al (2005) have shown that anxiety is related to low levels of HRV parasympathetic components during exposure to stressors. However, the results remain debatable (Dishman et al 2000;Narita et al 2007).…”
Section: Introductionmentioning
confidence: 99%